Tertiary treatment of biologically treated palm oil mill effluent (POME) using UF membrane system: effect of MWCO and transmembrane pressure - Idris, Abolore Munirat; Jami, Mohammed Saedi; Muyibi, Suleyman Aremu (World Academy of Research and Publication, 2010)
This study evaluate the performance of ultrafiltration UF membrane system in the treatment of biologically treated palm oil mill effluent (POME) by varying the effects of transmembrane pressure and using different molecular weight cut-off (MWCO). Flat sheet polyethersulfone (PES) ultrafiltration membrane of molecular weight cut-off (MWCO) 1 kDa and 5 kDa were used in this study. Biologically treated POME was subjected to physical pretreatment processes, consisting of coagulation and adsorption to remove total suspended solids. Transmembrane pressure was varied between 0.5 bar to 1.5 bar and the performance of these membrane systems were assessed in terms of reduction of chemical oxygen demand (COD), color and turbidity in POME. Pretreatment processes which consist of coagulation and adsorption showed remarkable results in reducing COD, color and turbidity up to 92.8 %, 99.3 % and 99.9 % respectively. At transmembrane pressure 0.5 bar, more reduction in COD, colour and turbidity were observed. The smallest MWCO of the membrane at transmembrane pressure 0.5 bar gave a better reduction of pollutants from the pretreated POME. The increasing transmembrane pressure leads to a corresponding increase in permeate flux which starts to level off at higher transmembrane pressures. The application of membrane separation technology to treat biologically treated POME has improved the quality of the final effluent discharged. The UF membrane plays very important role in reducing pollutants present in biologically treated POME.